Anti‐interleukin‐1 therapy has mild hypoglycaemic effect in type 2 diabetes. Issue 4 (26th November 2017) - Huang, Jinya; Yang, Yehong; Hu, Renming; Chen, Lili
Abstract : The aim of this study was to systematically evaluate the efficacy and safety of anti‐interleukin‐1 therapy for type 2 diabetes. A literature search of PubMed and Embase for available trials on anti‐interleukin‐1 therapy in type 2 diabetes was performed. The baseline characteristics, changes in HbA1c and other metabolic parameters, and adverse events were extracted from included randomized controlled trials (RCTs) and were analysed with Review Manager. Mean differences (MDs) and 95% confidence intervals (Cis) were calculated to measure differences in metabolic parameters. Odds ratio and 95% CIs were calculated for adverse event rates. Five RCTs were included in the current meta‐analysis with 357 subjects undergoing anti‐interleukin‐1 therapy (IL‐1 receptor antagonist or anti‐IL‐1beta antibody) and 221 controls who received placebo. The HbA1c decrement (%) of anti‐interleukin‐1 group was significantly higher than that of the placebo group (MD = 0.23; 95% CI, −0.39 to −0.07; P = .005). AUC of C‐peptide was improved also (MD = 14.55; 95% CI, 1.81‐27.28; P = .03) after anti‐interleukin‐1 intervention. There was no difference in the rate of adverse events (odds ratio, 1.16; 95% CI, 0.90‐1.49; P = .25) between 2 groups. Anti‐interleukin‐1 therapy has mild hypoglycaemic effect in type 2 diabetes.